INFLUENCE OF PARENTS’S MOTIVATION FOR STUDENT ACHIEVEMENT IN CLASS VII SMP NEGERI 6 Padangsidimpuan ACADEMIC YEAR 2015/2016 - Vitria Larseman Dela (Universitas Muhammadiyah Tapanuli Selatan, 2016)
The study is based on the problem of students still have difficulty in learning, the general problem of this research is